A Stopped Pilot Study of the ProGlide Closure Device After Transbrachial Endovascular Interventions. (October 2019) - Meertens, Max M.; de Haan, Michiel W.; Schurink, Geert W. H.; Mees, Barend M. E.
Purpose: To evaluate the feasibility and safety of the suture-mediated ProGlide device in closure of the brachial artery after endovascular interventions.Materials and Methods: From 2016 to 2017, a pilot study was performed using the ProGlide to achieve hemostasis after percutaneous access of distal brachial arteries >4 mm in diameter. In an interim analysis, the results were compared to a matched control group taken from a 60-patient historical cohort who underwent brachial artery access and manual compression to achieve hemostasis between 2014 and 2017. The primary outcome was access-related reintervention and the secondary outcome was the incidence of access-site complications.Results: Seven patients (mean age 67.9 years; 6 men) were enrolled in the study before it was stopped in 2017. Four patients experienced 6 access-site complications (neuropathy, hematoma, occlusion, and pseudoaneurysm). These resulted in 3 access-related reinterventions: surgical evacuation of a hematoma, thrombectomy of the occluded brachial artery, and surgical repair of the pseudoaneurysm. In the interim comparison to the 19 matched patients (mean age 61.9 years; 6 men), the ProGlide group had proportionally more patients experiencing access-related complications (57% vs 16% for manual compression, p=0.035) and resultant reinterventions (43% vs 11%, p=0.064). Based on this data the trial was stopped.Conclusion: Considering this experience, it is not advisable to use the ProGlide in transbrachial endovascular interventions due to the high incidence of complications and access-related reinterventions.